2019
DOI: 10.1002/wer.1198
|View full text |Cite
|
Sign up to set email alerts
|

Survey of full‐scale sidestream enhanced biological phosphorus removal (S2EBPR) systems and comparison with conventional EBPRs in North America: Process stability, kinetics, and microbial populations

Abstract: Sidestream EBPR (S2EBPR) is an emerging alternative process to address common challenges in EBPR related to weak wastewater influent and may improve EBPR process stability. A systematic evaluation and comparison of the process performance and microbial community structure was conducted between conventional and S2EBPR facilities in North America. The statistical analysis suggested higher performance stability in S2EBPR than conventional EBPR, although possible bias associated with other plant‐specific factors m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 85 publications
(163 reference statements)
3
42
3
Order By: Relevance
“…Compared to stage 2, the known GAO populations shifted to Candidatus Competibacter over Defluviicoccus with a relative abundance of 15.3-24.9% at stage 3. Factors that govern the changes in known GAO community composition remain unclear including SRT (Onnis-Hayden et al, 2020), C/P ratios (Majed and Gu, 2020) and carbon compositions (Shen and Zhou, 2016) have been evidenced to be associated with GAOs shifts. The accumulation of Defluviicoccus in the system may be due to the propionate in the feeding medium, which prefers propionate instead of acetate in order to maximize their production of PHAs with the same glycogen consumption (Dai et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to stage 2, the known GAO populations shifted to Candidatus Competibacter over Defluviicoccus with a relative abundance of 15.3-24.9% at stage 3. Factors that govern the changes in known GAO community composition remain unclear including SRT (Onnis-Hayden et al, 2020), C/P ratios (Majed and Gu, 2020) and carbon compositions (Shen and Zhou, 2016) have been evidenced to be associated with GAOs shifts. The accumulation of Defluviicoccus in the system may be due to the propionate in the feeding medium, which prefers propionate instead of acetate in order to maximize their production of PHAs with the same glycogen consumption (Dai et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced biological phosphorus removal (EBPR) has been widely applied in treating domestic wastewater, however, the application of EBPR for high-strength waste streams has hardly been explored. EBPR has been deemed as unsuitable due to the presumptions that the high-strength wastewater characteristics may not be suitable for polyphosphate accumulating organisms (PAOs), as well as concerns regarding the performance stability that are susceptible to microbial community competitions and other factors such as pH, temperature, solids retention time, influent carbon to phosphorus ratio and system configurations (Neethling et al, 2006, Onnis-Hayden et al, 2020). A limited number of studies using lab-scale EBPR reactors to treat synthetic high-strength wastewater showed promising overall P removal efficiency (~70%), but no process optimization and comprehensive evaluations of kinetics and mechanisms of the EBPR were performed in these studies (Bickers et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…After performance evaluation on two synthetic datasets with or without linear relationship, the proposed algorithm and method were applied to investigate sampling size requirements with single-cell Raman spectroscopic dataset retrieved from eight microbial communities representing eight different wastewater reuse and reclamation facilities (WRRFs) located in North America 27, 42 . Details on these EBPR facilities, sampling and SCRS data acquisition were described in the methods section and in supporting information.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, each sludge sample was independently performed a phosphorus release and uptake kinetics batch test as described by Gu et al (2008) 39 . Raman-based phenotypic survey was performed on the sludge extracted throughout the batch test following the preparing and acquisition protocol described by Majed et al (2008) and Onnis-Hayden et al (2019) [40][41][42] . All spectra were acquired with a 400-1800 cm -1 range which is often referred as the "fingerprint range" for various cellular or biomass substances 6,23,43 .…”
Section: Sample Size Assessmentmentioning
confidence: 99%
See 1 more Smart Citation